2021
DOI: 10.1080/10242422.2021.1882430
|View full text |Cite
|
Sign up to set email alerts
|

Activity and stability of hyperthermostable cellulases and xylanases in ionic liquids

Abstract: The biochemical conversion route in the utilization of biomass has required intensive development of processing methods for reducing recalcitrance of cellulose to enzymatic hydrolysis. Since discovering hydrophilic ionic liquids (ILs) are efficient lignocellulose solvents, considerable efforts have been made to demonstrate their potential applications in cellulose hydrolysis. However, most of the commercial lignocellulose hydrolyzing enzymes are largely deactivated or inhibited in the presence of even low conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 140 publications
(283 reference statements)
2
7
0
Order By: Relevance
“…PhEG was slightly activated in the presence of 40% [TMGH]n-PrCOO (Rahikainen et al 2018 ), and enzyme activation by ILs has also been observed in other hyperthermophilic endoglucanases (Hebal et al 2021 ). This phenomenon has been proposed to reflect the need for salt to achieve maximal enzyme activity (Ajloo et al 2013 ; Gladden et al 2014 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…PhEG was slightly activated in the presence of 40% [TMGH]n-PrCOO (Rahikainen et al 2018 ), and enzyme activation by ILs has also been observed in other hyperthermophilic endoglucanases (Hebal et al 2021 ). This phenomenon has been proposed to reflect the need for salt to achieve maximal enzyme activity (Ajloo et al 2013 ; Gladden et al 2014 ).…”
Section: Resultsmentioning
confidence: 95%
“…Dissolved cellulose can be precipitated away from the IL solution using an antisolvent. However, traces of ILs (in the range of 10–15%) may remain in the substrate after precipitation (Engel et al 2010 ), and most commercial cellulases are inhibited or deactivated by even low amounts of ILs (Wahlström and Suurnäkki 2015 ; Nemestóthy et al 2017 ; Hebal et al 2021 ). Therefore, the discovery or development of new enzymes with greater tolerance towards ILs is a prerequisite for the development of lignocellulose processes that use ILs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the activity in the 5 and 10 wt% VimC 3 S solutions was significantly higher than that in water. An increase in enzymatic activity in another IL-containing solution has been reported, 25 and this may be the case. Although the mechanism of this increase is unclear, and further analyses are needed to elucidate the precise mechanisms, we speculate that the ion interactions between ZIs and the surface charges of GnT-V possibly affect the structure of GnT-V.…”
mentioning
confidence: 83%
“…Metagenomics are widely used as very powerful techniques to identify, Isolate, and characterized novel thermostable enzymes with efficient catalytic activities from extreme environment which includes various environment that are usually characterized by extreme temperature like hot springs, deserts, compost, hydrocarbon reservoirs, hydrothermal vents, e. t.c. ( Zarafeta et al, 2016 ; Madhavan et al, 2017b ; Hebal et al, 2021 ). The ability of a microbes to survive in these extreme habitat makes their protein to be highly thermostable.…”
Section: Cellulase and Xylanase Of Thermophilesmentioning
confidence: 99%